Cichorium intybus Its Medicinal Properties - Qahramonova Shirmonoy Rafiqjon qizi; Saloxidinov Nurillo Mansurbek ogli (American Journal of Biodiversity, 2025)
Cichorium intybus commonly known as chicory, is a perennial herbaceous plant belonging to the Asteraceae family, widely recognized for its nutritional and medicinal value. Traditionally used since ancient times in various cultures for treating ailments ranging from digestive disorders to liver conditions, chicory contains a rich array of bioactive compounds, including inulin, sesquiterpene lactones (e.g., lactucin, lactucopicrin), phenolic acids (e.g., chicoric acid, chlorogenic acid), flavonoids, coumarins, and anthocyanins. These constituents contribute to its diverse pharmacological properties, such as antioxidant, hepatoprotective, anti-inflammatory, antidiabetic, antimicrobial, hypolipidemic, anticancer, gastroprotective, analgesic, and wound-healing effects. Preclinical studies, including in vitro assays and animal models, provide substantial evidence supporting these activities through mechanisms involving free radical scavenging, modulation of inflammatory pathways (e.g., NF-κB inhibition), improvement of glucose metabolism, and enhancement of gut microbiota. Recent reviews (up to 2025) highlight its potential in managing oxidative stress-related diseases, diabetes, and inflammation. Although generally safe at dietary levels, further high-quality clinical trials are essential to confirm efficacy, optimize dosages, and establish its role in modern evidence-based therapeutics. Chicory's versatility positions it as a promising candidate for functional foods, supplements, and novel drug development.